Les stratégies cartographiques des membres de la plateforme Technopolice.fr - Collectif du Préludde (M@ppemonde)
As a consequence of the transformation of the institutional frameworks of control and security, the spreading of videosurveillance in public space is today contested by several militant collectives that organize themselves through cartographic modes of action. Their practices aim to denounce, by making it visible, a new techno-security dimension of the power relations that structure space. Thanks to the results of a field survey conducted among the members of the cooperative platform Technopolice, we show that the strategic role of collaborative cartography in their political actions lies in its aggregative and multiscalar functions. The dissemination of maps and their production appear as complementary, analytical and symbolic means used by the activists to better understand and raise public awareness of the phenomenon they oppose.